Hybrid solar-driven interfacial evaporation systems: Beyond water production towards high solar energy utilization. (January 2021) - Ding, Tianpeng; Zhou, Yi; Ong, Wei Li; Ho, Ghim Wei
Graphical abstract: Abstract: Owing to its promising approach to tackling freshwater scarcity, solar-driven interfacial evaporation (SDIE) which confines the photothermal heat at evaporating surface has attracted tremendous research attention. Optimizing efforts on photothermal conversion and thermal management have greatly improved the SDIE performance. By taking advantage of the heat localization strategy, hybrid SDIE systems have been designed to enhance the solar energy utilization beyond water production. In this review, the development of SDIE and energy flow in hybrid system are discussed. The advanced conceptual designs of different hybrid applications such as electricity generation, fuel production, salt collection, photodegradation and sterilization are comprehensively summarized. Moreover, the current challenges and future perspectives of the hybrid systems are emphasized. This article aims to provide a systematic review on the recent progresses in hybrid SDIE systems to inspire both fundamental and applied research in capitalizing the undervalued auxiliary energy sources for future integrated water, energy and environmental systems.